KARAKTERISTIK HABITAT RAFFLESIA (Rafflesia tuan-mudae) DI GUNUNG POTENG CAGAR ALAM RAYA PASI KALIMANTAN BARAT - Erlinda, Asteria; Iskandar, .; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2018)
One of the plants endemic of West Kalimantan is Rafflesia Tuan-mudae. R. Tuan-mudae found at the Raya Pasi Nature Reserves in West Kalimantan, especially at Mount Poteng. Information about the habitat of R. Tuan-mudae at Mount Poteng is still not found. The purpose of this study was to get information about characteristics of habitat R. Tuan-mudae at Gunung Poteng Raya Pasi Nature Reserve. Data collection was carried out in May 2018, R. Tuan-mudae habitat analysis was carried out using a survey method. Data retrieval using observer plots was determined by purposive sampling technique. Using a double observation plot measuring 20 x 50 m, totaling 4 plots. The results of the study found 145 R. Tuan-mudae individuals, at an altitude between 431-503 masl, slope 18.25%, temperature 25 Â° C-26.1 Â° C with humidity between 83% -89%. This Rafflesia lives in the host plant Tetrastigma sp.Keywords: characteristics, habitat, Rafflesia Tuan-mudae